2017
DOI: 10.1007/s00449-017-1838-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimum spacing between electrodes in an air-cathode single chamber microbial fuel cell with a low-cost polypropylene separator

Abstract: The performance of a single chamber microbial fuel cell (MFC) with a low-cost polypropylene separator was investigated at various electrode interspaces in a separator electrode assembly (SEA). The lag period was shortened (3.74-0.17 days) and voltage generation was enhanced (0.2-0.5 V) as electrode spacing was increased from 0 to 9 mm. Power density was increased from 220 to 370 mW/m with increased spacing. The highest power density of 488 mW/m was obtained in polarization analysis with 6 mm. The oxygen mass t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The total internal resistance of an MFC proves to be another vital factor in determining the performance of the cell. The total internal resistance comprises an anode resistance, cathode resistance and ohmic resistance (in the case of membrane-less MFC) (Kondaveeti et al, 2017), The spacing between the electrodes contributes to the ohmic resistance, whereas the geometry or the structure of the anode and cathode affects the anode and cathode resistance. Hence, any change in the structure or spacing affects the resistance of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…The total internal resistance of an MFC proves to be another vital factor in determining the performance of the cell. The total internal resistance comprises an anode resistance, cathode resistance and ohmic resistance (in the case of membrane-less MFC) (Kondaveeti et al, 2017), The spacing between the electrodes contributes to the ohmic resistance, whereas the geometry or the structure of the anode and cathode affects the anode and cathode resistance. Hence, any change in the structure or spacing affects the resistance of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…This kind of membrane exhibited a relatively small internal ohmic resistances of 2-11 Ω. Higher performances (280 mW m −2 ) were achieved during 280-days operation with single-chamber bottle-type microbial fuel cells (Kondaveeti et al, 2018) and 488 mW m −2 was obtained in polarization analysis with 6 mm distance between electrodes in single-chamber MFCs (Kondaveeti et al, 2017). The architecture of components, indeed, plays a key role in facilitating the transport of ions between electrodes and membrane properties.…”
Section: Introductionmentioning
confidence: 94%
“…The PEM can prevent oxygen diffusion from the air cathode to the anode, thus preserving Materials 2024, 17, 1286 2 of 14 the anaerobic environment in the anode chamber. Studies have reported the use of various separation membranes to prevent oxygen diffusion from the cathode to the anode, including ultrafiltration membranes [11], permeable membranes [12], cathode ion exchange membranes [13], and modifications to the air cathode to limit oxygen diffusion [14,15].…”
Section: Introductionmentioning
confidence: 99%